Data-driven chronic care delivery pathways visualization Methods: protocol for a systematic review. (30th September 2020) - Siqueira do Prado, L; Allemann, S; Viprey, M; Schott, A-M; Dediu, D; Dima, A L
Abstract: Background: Faced with increasing illness burden and costs, healthcare systems are working towards integrated care to streamline services and improve efficiency, especially for chronic conditions. Routine care delivery data stored in various electronic healthcare databases (EHD) has the potential to support chronic care coordination if information is integrated and accessible at the point of care. Care delivery pathways (CDPs) can be constructed by linking multiple data sources and extracting time-stamped healthcare utilization events and other medical data related to individual or groups of patients over specific time periods; CDPs may facilitate communication on current practice and ways of improving it. We aim to identify and describe the methods proposed to quantify and visualize CDPs. Methods: A literature search was performed in PubMed (MEDLINE), Scopus, IEEE, CINAHL and EMBASE, without date restrictions. We will describe CPDs methods from 3 perspectives relevant for EHD use in long-term care: (1) clinical (what clinical information is used and how was it considered relevant?), (2) data science (how was the method developed and implemented?), and (3) behavioral (which behaviors and interactions are promoted among users and how?). Data extraction will be performed via deductive content analysis using selected frameworks, and inductive analysis to identify additional relevant features. We will compare these characteristics to identify common, infrequent, or missing features, and extract recommendations for future initiatives. Results: The literature search identified 2349 entries, currently under title and abstract selection by 4 coders. This study will produce a comparison and synthesis of clinical, data, and behavioral features of CDPs methods and derive recommendations for CDP construction. Conclusions: This review works towards a common basis for visualizing and quantifying CDPs across healthcare systems, an essential prerequisite for interoperable digital health. Key messages: Visual feedback on health care trajectories, especially for chronic conditions, may support informed decisions and planning future care episodes to advance towards person-centered integrated care. We describe and compare technical and clinical characteristics of visual feedback methods available for care pathways, and behaviors they may promote in care planning, to inform future initiatives.